Colonial Epistemological Reliance and the Marginalization of Indigenous Mushaf Traditions: Evidence from Contemporary Ulum al-Qur'an Scholarship - Ahmad Hawasi; Taofeeq Olamilekan Sanusi (Tribakti: Jurnal Pemikiran Keislaman, 2026)
This study examines the extent to which colonial epistemological structures continue to shape contemporary Ulum al-Qur'an, particularly in the field of mushaf studies. The study employed a cross-sectional quantitative survey involving 385 scholars and graduate students from twelve Islamic universities in Indonesia, Malaysia, Egypt, and Turkey. Data were collected using a 42-item Likert-scale instrument measuring three latent constructs: Colonial Epistemological Reliance (CER), Indigenous Tradition Marginalization (ITM), and Decolonial Awareness (DA). The proposed model was analyzed using Confirmatory Factor Analysis (CFA) and Structural Equation Modeling (SEM). The measurement model demonstrated satisfactory psychometric properties (χ²/df = 2.13, CFI = 0.94, TLI = 0.93, RMSEA = 0.048, SRMR = 0.051). Descriptive findings indicated relatively high levels of Colonial Epistemological Reliance (M = 3.78, SD = 0.82) and Indigenous Tradition Marginalization (M = 3.62, SD = 0.91), whereas Decolonial Awareness remained comparatively lower (M = 2.94, SD = 1.03). Structural analysis revealed that Colonial Epistemological Reliance significantly increased Indigenous Tradition Marginalization (β = 0.61, p < .001), while Decolonial Awareness significantly reduced both Colonial Epistemological Reliance (β = −0.43, p < .001) and Indigenous Tradition Marginalization (β = −0.38, p < .001). Cross-national analysis further identified significant differences in Colonial Epistemological Reliance across the four countries (F(3,381) = 8.74, p < .001, η² = .064), highlighting the influence of distinct historical and institutional trajectories. By operationalizing decolonization as measurable epistemological constructs, this study extends contemporary decolonial theory from philosophical critique to empirical verification and provides evidence for developing a more pluralistic and epistemically balanced framework for global Qur'anic manuscript studies.